The flow of goods and remittance in Sabah: An overview - Marja Azlima Omar; Fazli Abd. Hamid; Ramli Dollah (Sabah Society, 2006)
Relations between Sabah. the Philippines (southern Philippines) and Indonesia has existed for a long time. This relationship was initially based through various activities i.e. commerce and trade, culture and migration. However, with the creation of man-made country boundaries, the relationship has become limited through the restriction placed by the respective countries. Currently, immigration is being perceived as a major problem in Malaysia, associated with illegal immigrants originating from the Philippines and Indonesia. However with immigration, there is also the transboundary flow of goods and currency. This paper will focus on remittance and the flow of goods in the form of barter trade and smuggling from the year 1996 until present and its implications on Malaysia (Sabah).